A tolerancia hatása egyes almát fertőző gombafajok megjelenésére - Sólyom, Laura; Lengyel, Kálmán; Takács, András Péter (GEORGIKON FOR AGRICULTURE, 2023)
Our studies were carried out in Szabadság-puszta near Veszprém in an apple orchard between 08.04.-06.10.2022. The degree and intensity of powdery mildew infection of the Idared variety were determined on all trees in treated and untreated rows. For other apple cultivars (Luna, Bonita, Gála), 100 leaf samples were randomly collected to determine the powdery mildew and scab infection. 83 leaves and 14 fruits out of 100 leaf and fruit samples of the variety Gála were infested with scabs in the untreated area. No infected leaves were found in the treated area. Symptoms were observed only on three of the 100 investigated fruits. On the Idared variety, the incidence of powdery mildew infection was much higher in the untreated than in the treated area, but the level of infection was equally high. On the Luna variety, no scab or mildew symptoms were observed during the season due to high tolerance. In the case of the Bonita cultivar, at the end of the growing season, 62 among 100 leaf samples showed mildew symptoms, while no scab was observed on the variety.